Physical activity programs for older people in the community receiving home care services: systematic review and meta-analysis - Burton E (Dove Medical Press, 2019)
Elissa Burton,1 Kaela Farrier,1 Rose Galvin,2 Shanthi Johnson,3 N Frances Horgan,4 Austin Warters,5 Keith D Hill11School of Physiotherapy and Exercise Science, Curtin University, Perth, Western Australia, Australia; 2School of Allied Health, Faculty of Education and Health Sciences, Health Research Institute, University of Limerick, Limerick, Ireland; 3School of Public Health, University of Alberta, Edmonton, AB, Canada; 4School of Physiotherapy, Royal College of Surgeons in Ireland, Dublin, Ireland; 5Health Service Executive, Dublin North City and County Healthcare Organisation, Dublin, IrelandAbstract: The proportion of older adults is increasing around the world and most wish to live in their home until they die. To achieve this, many will require services in the home to remain living independently. To maintain function (ie, strength, balance, and endurance), physical activity needs to be undertaken on a regular basis, and is essential as a person ages. Unfortunately, as people age there is a tendency to reduce activity levels, which often leads to loss of function and frailty, and the need for home care services. This updated systematic review includes a mix of study methodologies and meta-analysis, and investigated the effectiveness of physical activity/exercise interventions for older adults receiving home care services. Eighteen studies including ten randomized controlled trials meeting the selection criteria were identified. Many of the studies were multi-factorial interventions with the majority reporting aims beyond solely trying to improve the physical function of home care clients. The meta-analysis showed limited evidence for effectiveness of physical activity for older adults receiving home care services. Future exercise/physical activity studies working with home care populations should consider focusing solely on physical improvements, and need to include a process evaluation of the intervention to gain a better understanding of the association between adherence to the exercise program and other factors influencing effectiveness.Keywords: exercise, physical function, community care, reablement, seniors